Posterior INFIX for Treating Unilateral Unstable Sacral Fractures. Issue 4 (27th March 2022) - Qi, Haotian; Geng, Xin; Yu, Xiaokun; Chen, Wenhuan; Jia, Jian; Tian, Wei
Abstract : Objective: To evaluate the clinical outcomes of the treatment of unilateral unstable sacral fractures by fixation with the posterior INFIX (posterior pelvic ring screw‐rod internal fxation). Methods: Data of 60 patients with unilateral unstable sacral fractures who underwent surgery from March 2013 to March 2020 were retrospectively analyzed according to the selection criteria. All patients were associated with anterior pelvic ring injuries, and the operations were performed by the same team of surgeons. According to the different types of internal fixation, the patients were divided into two groups, which both included 30 patients: the posterior INFIX group and iliosacral screw fixation group. The demographic and clinical data of the two patient groups, such as age, sex, sacral fracture types based on the Denis classification, operation time, amount of intraoperative bleeding, intraoperative fluoros copy time, Majeed pelvic score at final follow‐up, and quality of fracture reduction based on Mears and Velyvis's imaging classification criteria were collected by the same researcher and compared statistically. Results: All patients were continuously followed up for 23.17 ± 3.34 months (range, 12 to 46 months). All sacral fractures healed with an average healing time of 9.3 ± 2.24 months (range, 6 to 18 months). None of the patients had re‐displacement of the fracture or fixation failure. Compared to the iliosacral screw group, the posterior INFIX group patients had more intraoperative bleeding ( t  = 3.59, P  < 0.001), shorter operation time ( t  = 4.49, P  < 0.001), and shorter intraoperative fluoroscopy time ( t  = 6.26, P  < 0.001). There were no statistical differences between the two groups in terms of age, sex, fracture type, Majeed score, and quality of fracture reduction ( P  > 0.05). In the posterior INFIX group, one patient had a superficial wound infection and one patient complained of discomfort due to a prominent fixation. In the iliosacral screw fixation group, one patient had intraoperative iatrogenic S1 nerve injury and vessel injury. The posterior INFIX fixation was a simpler manipulation with higher safety, shorter time of operation and intraoperative fluoroscopy, and similar clinical outcomes compared to iliosacral screw fixation. Conclusion: For the treatment of unilateral unstable sacral fractures, the posterior INFIX fixation can be recommended in clinic application. Abstract : The posterior pelvic ring internal fixator (INFIX) screw‐rod system for treating the unilateral unstable sacral fracture.